Not too late : changing the climate story from despair to possibility - Solnit, Rebecca; Lutunatabua, Thelma Young; Solnit, David (Haymarket Books, 2023)
"Not Too Late brings strong climate voices from around the world to address the political, scientific, social, and emotional dimensions of the most urgent issue human beings have ever faced. Accessible, encouraging, and engaging, it's an invitation to everyone to understand the issue more deeply, participate more boldly, and imagine the future more creatively. In concise, illuminating essays and interviews, Not Too Late features the voices of Indigenous activists, such as Guam-based attorney and writer Julian Aguon; climate scientists, among them Jacquelyn Gill and Edward Carr; artists, such as Marshall Islands poet and activist Kathy Jeñtil-Kijiner; and longtime organizers, including The Tyranny of Oil author Antonia Juhasz and Emergent Strategy author adrienne maree brown. Shaped by the clear-eyed wisdom of editors Rebecca Solnit and Thelma Young Lutunatabua, and enhanced by illustrations by David Solnit, Not Too Late is a guide to take us from climate crisis to climate hope. Contributors include Julian Aguon, Jade Begay, adrienne maree brown, Edward Carr, Renato Redantor Constantino, Joelle Gergis, Jacquelyn Gill, Mary Annaise Heglar, Mary Ann Hitt, Roshi Joan Halifax, Nikayla Jefferson, Antonia Juhasz, Kathy Jetnil Kijiner, Fenton Lutunatabua & Joseph Sikulu, Yotam Marom, Denali Nalamalapu, Leah Stokes, Farhana Sultana, and Gloria Walton."--Publisher marketing.